PEMETAAN LOKASI KELUARGA PENERIMA MANFAAT PKH DI KECAMATAN PRAYA TENGAH MENGUNAKAN EXTENTION GEOPROCESSING - Sofiansyah Fadli; Fitri Rohyatul Aini (Jurnal Informatika dan Rekayasa Elektronik, 2018)
Based on data from UPPKH sub-district of Central Praya Year in 2017. The number of beneficiaries from the Government Program namely the Program Family expectations (PKH) and Beneficiary Families (KPM) is 3,425 which are spread throughout the villages in the Central Praya. The existence of the problems and constraints that have emerged is the difficulty the other escorts who are outside of the town would like to know the location and development of recipient PKH KPM. Extention Geoprocessing is a tool for processing spatial data in ArcView. The use of extension geoprocessing on the geographic information syste is one tool that can be used to assist in analyzing the condition and whereabouts of beneficiaries of government programs, especially the PKH KPM Program, especially in the Central Praya sub-district.The method used in analyzing data is the model SPIRAL method, the programming language used is PHP / MapScript, and criteria used are sourced from BPS. With the building of a geographic information system mapping the PKH KPM location, the community and the government will find it easier to know the development of poverty and can facilitate outside sub-district facilitators to find the location of PKH KPM in the central Praya sub-district.